Strategic Role of Social Media in Enhancing Customer Engagement in Higher Education - Hesti Umiyati; Asep Surahmat; Dhimas Tribuana; Lukas Umbu Zogara (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: The growth of social media has changed the communication space for colleges and universities, especially in conversations with prospective or enrolled students. To fill gap and also provide empirical basis, this study aims to investigate the strategic contribution of social media in developing customer engagement in Indonesian higher education setting focusing on content quality, engagement strategy, and platform diversity.Methodology: The research was carried out using the quantitative method of the descriptive type. Initial data was collected through an online survey that was sent to 150 strategically chosen participants who create content centred on university through platforms including Instagram and TikTok. The analysis was conducted with Partial Least Squares Structural Equation Modeling (PLS-SEM).Finding: From the findings of this research, three main constructs that underpin the impact of a socialmedia strategy on customer engagement were discovered: diversity; interaction and content quality. The effective communication, right choice of the platform and strategic methods of communication are important in maintaining the engaging.Conclusion: This analyses offer institutions a perspective of how to further develop the presence in social media, and is an effort to understand how students can be communicated with using digital channels within higher education. It highlights the necessity for academic programs to move from mere content delivery in a digital environment toward something more meaningful and engaging. It is recommended for future studies to use mixed-method design and compare the results, which can provide a full picture about such contexts.